EDUKASI PEMBUKUAN AKUNTANSI SEDERHANA SEBAGAI SOLUSI PENYUSUNAN LAPORAN KEUANGAN (Studi Kasus Pada Pelaku Usaha Mikro Kecil Menengah Desa Leran Kecamatan Manyar Kabupaten Gresik) - Aminin, Aminin; Febrianti, Erfiana; Kusniawati, Anisa; Heri Ningrum, Anita Romadhon; Cahyaningrum, Adinda Dwiki (Universitas Muhammadiyah Gresik, 2022)
Community service activities through socialization aim to provide knowledge and skills of simple accounting bookkeeping for Micro, Small and Medium Enterprises in Leran Village, Manyar District, Gresik Regency. The limited understanding of accounting, which is considered complicated, has resulted in the community as business actors being still minimal in compiling financial reports. The socialization activity of simple accounting bookkeeping was held as a means to help solve problems faced by MSME business actors due to their lack of understanding of accounting and financial reports. The form of activities carried out is by holding education through socialization, publication of financial statements, as well as question and answer discussions about simple accounting bookkeeping. This activity was given by students of the University of Muhammadiyah Gresik to provide information and increase knowledge about good and correct accounting records and preparation of financial reports. Financial reports can be used as information for decision making by various stakeholders, so this is very important to be applied even by MSME actors because it can realize sustainable business growth. Bentuk kegiatan yang dilakukan yaitu dengan mengadakan edukasi melalui sosialisasi, publikasi bentuk laporan keuangan, serta diskusi tanya jawab seputar pembukuan akuntansi sederhana. Kegiatan ini diberikan oleh mahasiswa Universitas Muhammadiyah Gresik guna sebagai bekal informasi dan meningkatkan pengetahuan tentang pencatatan akuntansi dan penyusunan laporan keuangan yang baik dan benar. Laporan keuangan dapat menjadi sebuah informasi dalam pengambilan keputusan oleh berbagai pemangku kepentingan maka hal ini sangat penting untuk diterapkan meski oleh pelaku UMKM karena dapat mewujudkan pertumbuhan usaha secara berkelanjutan.